The Effect of Germination Duration on the Biochemical Indicators and Functional-Technological Properties of Triticale Grain - Gulnazym Ospankulova; Indira Temirova; Dana Toimbayeva; Saule Saduakhasova; Sayagul Tazhina; Dina Khamitova; Marat Muratkhan; Akmaral Aldiyeva; Aibek Zhumalin (Applied Sciences)
Germination is a biotechnological process that activates enzymatic reactions and alters the chemical content of grain, improving its nutritional and functional value. However, the duration of the germination process significantly affects grain composition and properties. Prolonged and uncontrolled germination can lead to undesirable changes, such as excessive enzymatic activity, microbial contamination of sprouted grains, and loss of dry matter. While short-term germination is preferable for producing various food products, including whole-grain porridge, this article analyzed the impact of short-term germination of triticale grain (for 18, 20, 22, and 24 h) on its biochemical indicators and functional-technological properties. This research established that changes in biochemical values accompany the germination of triticale grain. The most significant increase in protein content was observed after 20 h of germination (GT 20), which increased by 4.43%. In contrast, after 24 h (GT 24), a decrease of 3.27% was noted compared to the original content in the whole grain (WGT). The contents of fats, carbohydrates, and ash tended to decrease. Germination promoted an increase in the amount of essential amino acids and improved the amino acid profile, particularly during the 20 and 22 h germination intervals. At 24 h of germination, the highest increase in total phenolic compounds (28.6%) and antioxidant activity (20.8%) was recorded. B-group vitamins, thiamine, and riboflavin, were detected in the sprouts only after 22 and 24 h of germination. The highest thiamine content (0.17 mg/kg) was observed at the 22nd hour, and the highest riboflavin content (2.51 mg/kg) was observed at the 24th hour. Niacin content showed a steady increase throughout the germination period. The maximum magnesium (0.200%) and molybdenum (0.589%) contents were recorded after 24 h of germination, while the calcium content increased at all germination intervals. The functional and technological properties of sprouted triticale grain improved, while the pasting (gelatinization) properties tended to decrease. Thus, it has been established that short-term germination enhances the biochemical indicators and functional-technological properties of triticale grains, indicating their potential for use in the production of whole-grain porridge.